Proteomic Analysis of Embryogenesis and the Acquisition of Seed Dormancy in Norway Maple (Acer platanoides L.) - Aleksandra Maria Staszak (International Journal of Molecular Sciences, 2014)
The proteome of zygotic embryos of Acer platanoides L. was analyzed via high-resolution 2D-SDS-PAGE and MS/MS in order to: (1) identify significant physiological processes associated with embryo development; and (2) identify changes in the proteome of the embryo associated with the acquisition of seed dormancy. Seventeen spots were identified as associated with morphogenesis at 10 to 13 weeks after flowering (WAF). Thirty-three spots were associated with maturation of the embryo at 14 to 22 WAF. The greatest changes in protein abundance occurred at 22 WAF, when seeds become fully mature. Overall, the stage of morphogenesis was characterized by changes in the abundance of proteins (tubulins and actin) associated with the growth and development of the embryo. Enzymes related to energy supply were especially elevated, most likely due to the energy demand associated with rapid growth and cell division. The stage of maturation is crucial to the establishment of seed dormancy and is associated with a higher abundance of proteins involved in genetic information processing, energy and carbon metabolism and cellular and antioxidant processes. Results indicated that a glycine-rich RNA-binding protein and proteasome proteins may be directly involved in dormancy acquisition control, and future studies are warranted to verify this association.